Archaeology at Aksum, Ethiopia, 1993-7 Volume 1 - Phillipson, David W. (Reports of the Research Committee of the Society of Antiquaries of London, 2000)
This two-volume work provides a detailed account of five seasons' archaeological research at Aksum, Ethiopia. Aksum was, during the first seven centuries AD, the capital of a major state, centred on the highlands of northern Ethiopia/Eritrea, which exercised a powerful influence on international trade. Christianity was adopted in the fourth century, and Aksum played a vitally important role in the rise of Ethiopian civilization. The reports describe royal tombs and commoner graves, domestic economy and international trade, monumental architecture and farming settlements, finely carved ivory and flaked stone tools.